2019
DOI: 10.1002/jbm.a.36780
|View full text |Cite
|
Sign up to set email alerts
|

Specific concentration of hyaluronan amide derivative induces osteogenic mineralization of human mesenchymal stromal cells: Evidence of RUNX2 and COL1A1 genes modulation

Abstract: Hyaluronic acid (HA) is an ideal material for tissue regeneration. The aim of this study was to investigate whether a hyaluronan amide derivative (HAD) can enhance the mineralization of human mesenchymal stem cells (hMSCs). Osteogenically induced hMSCs cultured with or without HAD at different concentrations (0.5 mg/ml or 1 mg/ml) were analyzed for mineral matrix deposition, metabolic activity, cellular proliferation, and the expression of 14 osteogenic genes. Unmodified HA (HYAL) was used as control. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…As shown by western blotting, Runx2 expression at day 14 was significantly lower than that at day 7. This trend was consistent with the results reported by Paolella et al [45]. Another study [46] has shown that Runx2 plays an important role in coordinating the multiple signals involved in osteoblast differentiation and is a specific transcriptional regulator necessary for osteoblast differentiation and bone formation.…”
Section: Discussionsupporting
confidence: 93%
“…As shown by western blotting, Runx2 expression at day 14 was significantly lower than that at day 7. This trend was consistent with the results reported by Paolella et al [45]. Another study [46] has shown that Runx2 plays an important role in coordinating the multiple signals involved in osteoblast differentiation and is a specific transcriptional regulator necessary for osteoblast differentiation and bone formation.…”
Section: Discussionsupporting
confidence: 93%
“…As shown by the Western blot results, the day 14 expression was significantly lower than on day 7. This trend is consistent with the results reported by Paolella et al [43]. Other studies [44] osteoblast differentiation and bone formation.…”
Section: Discussionsupporting
confidence: 93%
“…Among them, COL1A1 and SPP1 were contained as proteins that increase during spaceflight. COL1A1 are early markers of osteoblast differentiation, while SPP1 (osteopontin) appears later, concomitantly with mineralization [39]. In this study, SPP1 serum levels increased about 1 month after launch (F‐2) and remained high during spaceflight (F‐3 and F‐4) and for about 1 month after return to Earth (R‐3), although there were large intersample differences (Figure 3).…”
Section: Resultsmentioning
confidence: 56%
“…Thus, SPP1 may be a protein whose serum levels change in response to microgravity in space. Furthermore, serum levels of POSTN, an osteogenic marker expressed from early to mid‐life [39], decreased significantly immediately after launch (F‐1) but its profile thereafter resembled that of COL1A1 (Figure 3). Namely, the proteomic profiles of these bone metabolism related‐proteins, including ALPL, revealed that the serum levels of each protein after return to Earth from prolonged spaceflight were more variable than preflight, peaking at approximately 1 month after the flight (R‐3).…”
Section: Resultsmentioning
confidence: 99%